Experimental study on gas permeability characteristics of Biochar-Amended Loess - Zhao Wenqi; Li Xi-An (E3S Web of Conferences)
Gas permeability is an important parameter to characterize the permeability and structure of soil. In this paper, the air permeability test of Mâlain loess with different water content and biochar content is carried out by using the improved air permeability meter, and the pore characteristics of the sample are Quantitative analysis from the microscopic level. The test results show that the gas permeability coefficient of soil increases first and then decreases with the increase of water content, and reaches the maximum at 16%. With the increase of biochar content, the gas permeability coefficient of soil decreases first and then increases, and there is an optimal content of biochar in the modified loess. The probability division index of pore area increases first and then decreases, and the average pore area decreases first and then increases the frequency of pore orientation is the largest in the range of 0° to 10°, the overall performance is anisotropic, and there is a dominant direction in the local area. The roundness of pores is concentrated in the range of 0.3 to 0.4, and the shape of pores is mainly irregular.